Development and validation of spectrophotometric and spectrofluorimetric methods for simultaneous determination of Tofisopam - Nesrin K. Ramadan, Afaf Osman, Roaida Fooad, Azza A. Moustafa (Journal of Applied Pharmaceutical Science)
Two simple, rapid and accurate spectrophotometric and spectrofluorimetric methods developed for the determination of Tofisopam (TF) in pure form and in pharmaceutical formulation. The spectrophotometric method (A) is based on the reduction of ferric into ferrous in presence of 1, 10-phenanthroline to give an orange –red colored ferroin complex measured at 510 nm. Method (B) spectrofluorimetric method is based on the oxidative coupling reaction of TF with 3-methylbenzothiazolin-2-one hydrazone (MBTH) hydrochloride in presence of cerium (IV) ammonium sulfate in an acidic medium. The quenching effect of TF on the fluorescence of excess cerous ions is measured at the emission λem 345 nm with excitation λex at 296 nm. The factors affecting the reactions were carefully studied and optimized. Beer,s law is obeyed in the range of 2-12 µg ml-1 for both methods with the mean percentages recovery of 100.04 ± 0.445 and 99.29 ± 0.563 for method (A) and (B), respectively. The two proposed methods were successfully applied for the determination of TF in Nodeprine tablets. Statistical comparison between the results obtained by these methods and that obtained by the official method for the determination of the drug was done, and it was found that there was no significant differences between them.
Keywords: Spectrophotometry, spectrofluorimetry,Tofisopam,O-phenanthroline,MBTH